2020
DOI: 10.1093/jrr/rraa036
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotherapy in pulmonary large cell neuroendocrine carcinoma: propensity score matching analysis

Abstract: Abstract The aim of the study was to investigate the survival advantage of radiotherapy (RT) in patients with pulmonary large cell neuroendocrine carcinoma (LCNEC). Patients with pulmonary LCNEC were extracted from the Surveillance, Epidemiology, and End Results (SEER) dataset between January 2004 and December 2013. Propensity score matching (PSM) analysis with 1:1 was used to ensure well-balanced characteristics of all comparison groups. A total of 1480 eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…Furthermore, the role of post-operative RT was evaluated in two large retrospective trials among patients with resected early-stage LCNEC, demonstrating that RT was not associated with survival benefit [ 63 , 64 ]. On the contrary, a recent large-population based study including 1480 LCNEC patients showed that RT could yield a survival benefit in patients with stage II-III LCNEC, a tumor size of 5–10 cm, and who had not been treated with surgery or were among patients who received chemotherapy [ 71 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, the role of post-operative RT was evaluated in two large retrospective trials among patients with resected early-stage LCNEC, demonstrating that RT was not associated with survival benefit [ 63 , 64 ]. On the contrary, a recent large-population based study including 1480 LCNEC patients showed that RT could yield a survival benefit in patients with stage II-III LCNEC, a tumor size of 5–10 cm, and who had not been treated with surgery or were among patients who received chemotherapy [ 71 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Brain metastasis rate and brain metastasis-free survival rate were significantly better than those for SCLC, with or without PCI. Notwithstanding, older age, primary location (main bronchus), and no adjuvant chemotherapy have been shown to exhibit significant associations with poor prognosis in previous studies [7,10]. LCNEC has been regarded as a disease entity that shows features of both NSCLC and SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most appropriate regimen (whether to follow the NSCLC-regimen or SCLC regimen) and the schedule of them are still not established, independently of the clinical stage of LCNEC [8]. Furthermore, the role of radiotherapy as post-operative treatment of local or advanced pulmonary LCNEC remains unclear, but some have suggested its use in the locally advanced disease setting [9,10]. Some researchers have recently proposed the need for prophylactic cranial irradiation (PCI) for this disease entity, based on its dismal prognosis and its high rate of brain metastasis, similar to SCLC, but a consensus has yet to be reached [10].…”
Section: Introductionmentioning
confidence: 99%
“…Luego, verificar que las covariables estén equilibradas entre el grupo de intervención o exposición y el de control de la nueva muestra emparejada. Finalmente, realizar un análisis multivariado sobre la base de la nueva muestra [23][24][25][26] (Figura 5).…”
Section: ¿Cómo Funciona?unclassified
“…La estimación de las PP se puede realizar en paquetes estadísticos tradicionales, recomendándose el uso de "R" y "STATA" 22,[27][28][29] . Sin embargo, también hay evidencia del uso de SAS y SPSS 22,25,26,28,29 .…”
Section: ¿Cómo Funciona?unclassified